Gefitinib-induced skin ulceration in metastatic adenocarcinoma lung - Vishwanath Sathyanarayanan; Kadabur Nagendrappa Lokesh; Lakshmaiah Kuntejowdahalli Channaviriappa; Linu Abraham Jacob (Indian Journal of Medical and Paediatric Oncology)
We report a case of gefitinib-induced skin ulceration in a 50-year-old female with metastatic adenocarcinoma of lung who developed this adverse effect 2 weeks following initiation of gefitinib at a dose of 250 mg/day. The ulcer improved with stopping gefitinib for 2 weeks and also addition of topical steroids and antibiotics. We are reporting this case to create awareness among treating oncologists of this adverse effect and also prompt interruption of therapy and topical steroids/antibiotics is useful to treat this adverse event.